Bermain Peran “Pelangi di Sekolahku” untuk Meningkatkan Pengetahuan Toleransi Anak Usia Prasekolah - Rusmaladewi, Rusmaladewi; Martani, Wisjnu (HUMANITAS, 2014)
ABSTRACTAs an archipelago country, Indonesia has 1.128 tribes, therefore, Indonesia has a lot of cultures, languages, races, religions and customs. This diversity if it is not well managed, is able to be the source of conflict. As the effort of preventing the conflict, since the early age of children, it is better to give them knowledge of tolerance. The objective of this research is to carry out the validation of role playing module “Pelangi Di Sekolahku” towards the knowledge of tolerance on the early age of children particularly the kindergarten students. The participants of this research were 32 kindergarten children. The participants were separated into control group (18 children) and experiment group (14 children). The hyphotesis of this research was that the role playing module “Pelangi Di Sekolahku” was able to improve the knowledge of tolerance on the early age of children. The method of the research used untreated control group design with pretest and posttest. The result of the statistical test which used mixed anava showed that there was the significantly difference between experiment group and control group with sig (0.000) < 0.01. The effective contribution of the role playing on the experiment group was 79.1%.Key words : Tolerance, Role playing, Preschool Children